Exchange rates and long-term bonds - Annika Alexius; Peter Sellin (Uppsala University, Department of Economics, 2002)
Tentative evidence suggests that the empiricalfailure of uncovered interest parity (UIP) is confined to short-term interest rates. Tests of UIP for long-term interest rates are however hampered by various data problems. By focusing on short investments in long-term bonds, these data problems can be avoided. We study the relationship between the US dollar - Deutsch Mark exchange rate and German and American bond rates. The hypothesis that expected returns to investments in bonds denominated in the two currencies are equal cannot be rejected. This result is not simply due to low power as the beta-coefficients are close to unity. For the corresponding short-term interest rates, the typical finding of a large and significantly negative beta-coefficient is confirmed.
urn:nbn:se:uu:diva-2227
Keywords: F31; F41; 330; Long-term interest rates; exchange rates; uncovered interest parity; Zinsparität; Zinsstruktur; Wechselkurs